Depression and Its Association With Self-Esteem and Lifestyle Factors Among School-Going Adolescents in Kuala Lumpur, Malaysia - Ibrahim, Mohamad Faez; Wan Ismail, Wan Salwina; Nik Jaafar, Nik Ruzyanei; Mohd Mokhtaruddin, Ummi Kalthum; Ong, Hooi Yee; Abu Bakar, Nur Hidayah; Mohd Salleh Sahimi, Hajar (Frontiers in Psychiatry, 2022)
Introduction Depression is a prevalent mental health condition worldwide and in Malaysia. Depression among adolescents has been steadily increasing. Self-esteem has been known to be associated with depression. It has been postulated that a poor lifestyle among adolescents is associated with depression. This paper aims to study the correlation of self-esteem, lifestyle (eating behavior, physical activity, and internet usage) with depression among Malaysian youth. Methodology This is a cross-sectional study among secondary school children from 5 random schools in an urban city of Kuala Lumpur, Malaysia. Those with intellectual disability and/or difficulty to comprehend Malay language, and without parental consent and assent, were excluded. Students from randomly selected classes aged 13-year-old to 17-year-old were invited to fill in these questionnaires: Socio-demographic Questionnaire, Rosenberg Self-esteem Questionnaire, Physical Activity Questionnaire (PAQ-A), Eating Disorder Examination Questionnaires (EDE-Q), Internet Addiction Test Scale (IAT), and Children's Depression Inventory (CDI). Result 461 students participated in the study. 21.5% of the participating students were found to have depression (n = 99). Younger age and Chinese race showed significant association with adolescent depression with a p-value of 0.032 and 0.017 respectively. Other significant correlations with depression were self-esteem (p = 0.013), disordered eating (p = 0.000), lower physical activity (p = 0.014) and problematic internet usage (p = 0.000). Discussion The prevalence of depression among adolescents in this study (21.5%) is in line with previous prevalence studies in Malaysia. Self-esteem is postulated to be a moderating factor for depression hence explaining the significant association. A sedentary lifestyle may increase the risk of developing depression, The causal relationship between problematic internet usage and depression is complex and difficult to establish. This is similar to the relationship between problematic eating behavior and depression as well. Conclusion There is still a need to explore the causal relationship between lifestyle factors and depression among youth. Despite that, the results from this paper have accentuated the gravity of the importance of a healthy lifestyle among adolescents. An appropriate preventive measure is governmental strategies and policies aiming at improving a healthier lifestyle in this age group.